Self-existence and Narcissistic Behavior (Generation Z Student) At Indo Global Mandiri University, Palembang City in Tiktok - Trizki Vera Anggraini; Yoyok Hendarso; Ridhah Taqwa (PT Mattawang Mediatama Solution, 2023)
This study investigates the self-existence and narcissism behavior among Generation Z female students at Indo Global Mandiri University in Palembang City, specifically focusing on their interactions on the social media platform TikTok. The research aims to understand the extent to which these young women engage in self-promotion and exhibit narcissistic tendencies within the context of their virtual presence. Through a mixed-methods approach combining surveys and content analysis of TikTok posts, the study explores the factors driving their behavior and assesses the potential consequences on their overall well-being and relationships. The findings shed light on the influence of social media on the self-identity and self-presentation of this demographic, offering valuable insights for educators, parents, and mental health professionals seeking to comprehend and address the implications of digital self-expression on the younger generation's psychosocial development.